From protests to polls: A study on voting intentions in Lebanon - Charles Harb (6709490) (2024)
This study examines collective action intentions in Lebanon, a country characterized by fragmented demographics and recent sociopolitical turmoil. Through a nationally representative survey of 1200 Lebanese individuals conducted just before national elections, we explore the impact of sociopolitical orientations, emotions, and social cohesion factors on voting intentions and collective action. The findings reveal significant emotional distress among the population, widespread distrust in political institutions, and varying degrees of political engagement influenced by sociodemographic factors such as wealth and education. Notably, the study challenges conventional collective action theories by showing the limited predictive power of social identities for voting behavior, instead highlighting the influence of individuals' social networks and emotional states on their political action intentions. This research contributes to the understanding of political engagement in volatile contexts, offering insights into the complex dynamics of collective action and voting behavior in Lebanon. Other Information Published in: Political Psychology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1111/pops.13072